RANCANG BANGUN PEMBANGKIT LISTRIK TENAGA SAMPAH (PLTSa) DI LINGKUNGAN STT MIGAS BALIKPAPAN - Nurjanah Nurjanah; A.M. Miftahul Huda; Riza Hadi Saputra; Ain Sahara; Hasanudin Hasanudin (Sekolah Tinggi Teknologi MIGAS, 2021)
The Environment and Forestry Metrics stated that data on waste piles in Indonesia in 2020 reached 67.8 tons, 45% of which was poorly managed plastic waste. The large amount of waste produced causes Indonesia to become the second waste producer in the world. The level of waste management that is still minimal is the main thing that causes Indonesia to become a